2015
DOI: 10.1007/s00432-015-1917-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor cell surface lysosome-associated membrane protein-1 (LAMP1) and its associated carbohydrates in lung metastasis

Abstract: PolyLacNAc on B16F10 cells and galectin-3 on lungs are the major participants in melanoma metastasis. Although surface LAMP1 promotes interactions with organ ECM and BM, carbohydrates on LAMP1 play a decisive role in dictating lung metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Our studies on a number of cancer cell lines proved that LAMPs on the cell surface served as adhesive glycoproteins participating in the complex process of tumor invasion and metastasis . This idea was supported by evidence for surface LAMP‐1 that promotes interactions with the extracellular matrix and basement membrane thus facilitating lung metastasis in melanoma . The overexpression of LAMP‐1 in our cases might reflect high metastatic potential of the tumor.…”
Section: Discussionsupporting
confidence: 72%
“…Our studies on a number of cancer cell lines proved that LAMPs on the cell surface served as adhesive glycoproteins participating in the complex process of tumor invasion and metastasis . This idea was supported by evidence for surface LAMP‐1 that promotes interactions with the extracellular matrix and basement membrane thus facilitating lung metastasis in melanoma . The overexpression of LAMP‐1 in our cases might reflect high metastatic potential of the tumor.…”
Section: Discussionsupporting
confidence: 72%
“…LAMP1 encodes a glycoprotein and is responsible for maintaining lysosomal integrity. The expression of LAMP1 has been observed on the surface of tumor cells from highly metastatic cancers, suggesting its role in the progression of lung cancer, colon cancer, and melanoma [60]. Surprisingly, LAMP2, another glycoprotein closely related to LAMP1, was up-regulated in BDE-99 exposed cells ( Fig 8D).…”
Section: Enriched Canonical Pathways Following Exposure To Bde-99mentioning
confidence: 91%
“…LAMP1 (CD107a) is a member of a family of membrane glycoproteins, expressed in all tissue types. Previous studies demonstrated that LAMP proteins mediate cell adhesion, migration and cancer metastasis (73,74). CD59, another candidate for further validation, is a GPI-anchored and lipid raft-localized glycoprotein of the LY6/uPAR family, similar to TEX101.…”
Section: Discussionmentioning
confidence: 99%